The stability under longitudinal compression of flat symmetric corrugated-core sandwich plates with simply supported loaded edges and simply supported or clamped unloaded edges - Seide, Paul (National Advisory Committee for Aeronautics, 1952)
A theory for the elastic behavior of orthotropic sandwich plates is used to determine the compressive buckling-load parameters of flat symmetrical corrugated core sandwich plates with simply supported loaded edges and simply supported or clamped unloaded edges.
"Langley Aeronautical Laboratory."
Date of issue: April 1952.
Report no. NACA-TN-2679.
Keywords: Plates (Engineering); Sandwich construction.; Loads (Mechanics); Buckling (Mechanics); Elasticity.; elektronické knihy; electronic books